1978
DOI: 10.1107/s0021889878013692
|View full text |Cite
|
Sign up to set email alerts
|

Direct X-ray determination of the electron-density profile of the nerve myelin membrane, with paracrystalline lattice distortions taken into account

Abstract: Paracrystalline lattice distortions in the nerve myelin membrane system lead to the distortion of the Q function of the membrane stack and the Qo function of the unit cell. The Q function can be expressed as a convolution polynomial of the electron density distribution and the distance-statistics functions between neighbouring membranes. Fitting this model Q function to the experimental Q function in a non-linear least-squares refinement procedure, one obtains the electrondensity profile of the myelin stack an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Such a refinement for fitting an entire intensity distribution has been successfully used for the analysis of powder patterns (Young et al, 1980;Wiles and Young, 1981) and for biological membranes (Funk et al, 1981). A least squares procedure has also been applied to the generalized Patterson function (Q-function) of biological membranes including nerve myelin (Pape et al, 1977;Gbordzoe and Kreutz, 1978). In the present work we found that the least squares procedure allowed us to optimize the parameters after relatively few…”
Section: Analysis Of Myelin Diffraction Patternsmentioning
confidence: 77%
“…Such a refinement for fitting an entire intensity distribution has been successfully used for the analysis of powder patterns (Young et al, 1980;Wiles and Young, 1981) and for biological membranes (Funk et al, 1981). A least squares procedure has also been applied to the generalized Patterson function (Q-function) of biological membranes including nerve myelin (Pape et al, 1977;Gbordzoe and Kreutz, 1978). In the present work we found that the least squares procedure allowed us to optimize the parameters after relatively few…”
Section: Analysis Of Myelin Diffraction Patternsmentioning
confidence: 77%